2022
DOI: 10.3389/fphar.2022.1008976
|View full text |Cite|
|
Sign up to set email alerts
|

Improved diagnosis of inflammatory bowel disease and prediction and monitoring of response to anti-TNF alpha treatment based on measurement of signal transduction pathway activity

Abstract: Objective: Ulcerative colitis (UC) and Crohn’s disease (CD) are two subtypes of chronic inflammatory bowel disease (IBD). Differential diagnosis remains a challenge. Anti-TNFα treatment is an important treatment for IBD, yet resistance frequently occurs and cannot be predicted. Consequently, many patients receive ineffective therapy with potentially adverse effects. Novel assays are needed to improve diagnosis, and predict and monitor response to anti-TNF-α compounds.Design: Signal transduction pathway (STP) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Very recently, it was found that the proportion of plasma cells at baseline could predict anti-TNF therapy response in two independent cohorts with an accuracy of 82% [27], and non-responders for either IFX or VDZ had increased abundance of neutrophils and activated CD4 + T cells before treatment [68]. Similarly, specific signalling pathways, namely NFκB, TGF-β or JAK-STAT, were enriched at baseline in non-responders IFX-or VDZtreated patients [69,70]. Altogether, these studies highlight the enormous potential and versatility of transcriptomic data for biomarker identification.…”
Section: Transcriptomic-derived Data Is Boosting Predictive and Perso...mentioning
confidence: 99%
“…Very recently, it was found that the proportion of plasma cells at baseline could predict anti-TNF therapy response in two independent cohorts with an accuracy of 82% [27], and non-responders for either IFX or VDZ had increased abundance of neutrophils and activated CD4 + T cells before treatment [68]. Similarly, specific signalling pathways, namely NFκB, TGF-β or JAK-STAT, were enriched at baseline in non-responders IFX-or VDZtreated patients [69,70]. Altogether, these studies highlight the enormous potential and versatility of transcriptomic data for biomarker identification.…”
Section: Transcriptomic-derived Data Is Boosting Predictive and Perso...mentioning
confidence: 99%
“…It is widely recognized UC mainly affects colon and rectum, while CD Crohn’s disease may involve the entire intestine, from mouth to anus (Bouwman et al ., 2022 ; Li et al ., 2022). It is often difficult to formulate a differential diagnosis, remaining this goal crucial for the appropriate treatment and management of these two pathologies (Bouwman et al ., 2022 ). IBDs inspired high quality research from all the world to deeply understand their underlying etiopathogenesis, course and outcome of such diseases.…”
Section: Introductionmentioning
confidence: 99%